Efficacy and safety of low-dose rituximab in the treatment of myasthenia gravis: a systemic review and meta-analysis - Yang, Xishuai; Zhang, Wei; Guo, Junhong; Ma, Chunlin; Li, Bingxia (Frontiers in Neurology, 2024)
Background Rituximab (RTX) is a monoclonal antibody that has been increasingly used in the treatment of myasthenia gravis (MG). In most studies, the therapeutic protocol of RTX has been similar to that adopted for B cell lymphoma, with an increasing number of studies aimed at exploring the efficacy of low-dose RTX in MG. However, the beneficial effects of low-dose RTX in MG remain a subject of critical debate. Methods This study was conducted following the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidelines. Two reviewers (Xishuai Yang and Bingxia Li) independently conducted searches across multiple databases, including PubMed, MEDLINE, EMBASE, Web of Science, Cochrane Library, and China National Knowledge Infrastructure (CNKI). A meta-analysis, utilizing representative forest plots, was performed to assess “Improved clinical status” and changes in the Quantitative Myasthenia Gravis (QMG) score before and after treatment. Results A total of 17 studies involving 292 patients were included in the meta-analysis. A noticeable improvement in clinical status was observed in 91% of patients at the final follow-up after therapy (95% CI: 84–96%, P < 0.001). The QMG score showed a significant reduction following the treatment, with a standardized mean difference (SMD) of −1.69 (95% CI: −2.21 to −1.16, Z = 6.29, P < 0.001). In the acetylcholine receptor antibody-positive myasthenia gravis (AChR-MG) group, 90% of patients achieved improved clinical status (95% CI: 80–97%, P < 0.001) and the QMG score significantly decreased after low-dose RTX treatment, with an SMD of −1.51 (95% CI: −0.80 to −2.21, Z = 4.50, P < 0.001). In the muscle-specific kinase antibody-positive myasthenia gravis (MuSK-MG) group, 97% of patients achieved improved clinical status (95% CI: 89–100%, P < 0.001). The QMG score also significantly decreased following low-dose RTX treatment, with an SMD of −2.31 (95% CI: −2.99 to −1.62, Z = 6.60, P < 0.001). Adverse effects were reported in 29 out of 207 patients (14%, including infusion reactions in 22 patients (10.1%), infections in three patients (1.45%), cytopenia in two patients (0.96%), eosinophilia in one patient (0.48%), and hemiplegia in one patient (0.48%). Additionally, one patient (0.48%) succumbed to complications from invasive thymoma. Conclusion Our meta-analysis shows that low-dose RTX is both effective and safe for treating MG. Systematic Review Registration PROSPERO, identifier: CRD42024509951.